2018
DOI: 10.1007/s00705-018-4089-y
|View full text |Cite
|
Sign up to set email alerts
|

Avian hepatitis E virus is widespread among chickens in Poland and belongs to genotype 2

Abstract: Big liver and spleen disease, caused by avian hepatitis E virus, has been reported in Poland, but the prevalence of the virus has not yet been investigated. In this study, 1034 serum samples from 57 breeder broiler and laying hen flocks were screened for the presence of anti-aHEV antibodies. In a random serology study, 56.1% of flocks were positive. Seroprevalence was higher in laying hen flocks than in broiler breeder flocks. Phylogenetic analysis of partial ORF1 and ORF2 sequences revealed that all Polish is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…This figure shows that the avian HEV strains from Korea are part of genotypes 1 and 2 of Orthohepevirus B, which was previously thought to only include avian strains from Australia and the USA; in contrast, the Chinese and Taiwanese avian strains are part of genotypes 3 and 4, respectively, which were previously thought to only include avian strains from Hungary. The members of Orthohepevirus B are associated with big liver and spleen disease and hepatitis-splenomegaly syndrome [77].…”
Section: Taxonomymentioning
confidence: 99%
“…This figure shows that the avian HEV strains from Korea are part of genotypes 1 and 2 of Orthohepevirus B, which was previously thought to only include avian strains from Australia and the USA; in contrast, the Chinese and Taiwanese avian strains are part of genotypes 3 and 4, respectively, which were previously thought to only include avian strains from Hungary. The members of Orthohepevirus B are associated with big liver and spleen disease and hepatitis-splenomegaly syndrome [77].…”
Section: Taxonomymentioning
confidence: 99%
“…There is a 20% positive rate for anti-avian HEV antibodies in chickens from Brazil (Vitral et al, 2005), and in Spain, positive rates for farms span a wide range from 20 to 80% (Peralta et al, 2009). In China, the avian HEV seropositive rate in chicken flocks is 35.9% (Zhao et al, 2013a), while in Poland, there is a 56.1% positive rate for avian HEV genotype 2 among breeder broiler and egg laying hen flocks (Matczuk et al, 2019). In the United States between the years 2012 and 2014, 141 chickens from 10 organic layer flocks showed a 40% decrease in the rate of egg production and slightly increased mortality (up to 1% per week), avian HEV RNA was detected in 10 livers out of 141 chickens from two different affected flocks (Crespo et al, 2015).…”
Section: Epidemiologymentioning
confidence: 99%
“…Genotype 1, was primarily isolated from BLS chickens in Australia and was also reported to cause the decrease in egg production in chickens during an outbreak in Korea (Payne et al, 1999; Kwon et al, 2012). Genotype 2, was primarily isolated from HSS chickens in the United States and was detected in BLS flocks in Central Europe and Poland, and also isolated from chickens with hepatitis-splenomegaly syndrome in Korea (Haqshenas et al, 2001; Moon et al, 2016; Matczuk et al, 2019). Genotype 3, was isolated from HSS chickens in Europe and from hens with decreased egg laying in China (Morrow et al, 2008; Zhao et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This study also shows that other animal species including chickens and wild boar, already identified as a reservoir of HEV are not yet studied in Africa. It is therefore necessary to perform investigations in these animals [ 64 69 ].…”
Section: Discussionmentioning
confidence: 99%